Leaking Like a Sieve? Transfer Restraints on Small Arms, Light Weapons and Ammunition. (22nd April 2019) - Alley, Roderic
Abstract: Compared to nuclear weapons, chemical and biological weapons or advanced conventional weapons systems, such as missiles, small arms and light weapons (SALW) and the ammunition required to render them lethal, have received less attention from arms control analysts. Accordingly the focus of this commentary is upon two particular inadequacies identified within the existing SALW restraint repertoire. They include, first, a failure to have SALW ammunition designated as an objective deserving explicit restraint designation and, secondly, persisting and largely unresolved state differences over controlling supplies of this weaponry to armed non-state actors. Both concerns illustrate how a use of consensus procedures within relevant rule formulation has favoured the interests of major SALW suppliers. The two deficiencies identified are considered destabilising given their continued capacity to degrade restraints designed to restrict deployments of this long-lasting weaponry—particularly within locations exhibiting limited forms of state capacity. The scope for existing legal mechanisms to remedy these deficiencies is examined, as is their potential to induce enhanced compliance and implementation.